The village is like a wheel : rethinking cargos, family, and ethnicity in highland Mexico - Magazine, Roger, 1969- (University of Arizona Press, 2012)
The author argues for a major shift in the prevailing approach to the study of rural highland peoples in Mexico. Using ethnographic material, the author builds a convincing case that many of the discipline's usual topics and approaches distract anthropologists from what is truly important to the people whose lives they study. While Western anthropologists have usually focused on the production of things, such as community, social structure, cultural practices, identities, and material goods - since this is what they see as the appropriate objective of productive action in their own lives - residents of rural highland communities in Mexico (among others) are primarily concerned with what the author calls "the production of active subjectivity in other persons." Rural highland Mexicans, he explains, see persons as inherently interdependent and in need of others.